A social history of Quakers in Scotland, 1800-2000 - Burton, Paul F. (Mellen, 2007)
Introduction: The Society of Friends in the nineteenth and twentieth centuries -- The secularisation XE "secularisation" debate -- Class and religion -- Quakerism and class -- Evangelicalism -- Quaker historiography -- XE "historiography" -- Quakerism now -- Quakerism in Britain : the historical background -- The seventeenth century -- The eighteenth century -- The nineteenth century -- The twentieth century -- Women in the society -- Occupations and Quaker businesses -- Quakerism in Scotland : the historical background -- The seventeenth century -- The eighteenth century -- The nineteenth century -- The twentieth century -- Migration and social change in the society in Scotland during the eighteenth and nineteenth centuries -- Scottish migration and emigration -- Certificates of removal -- XE "Quakers : migration patterns" Quaker migration -- The eighteenth century -- The nineteenth century -- Out-migration : certificates issued -- In-migration : certificates received -- Occupational change in the society in Scotland during the nineteenth century -- Occupational analysis of English Quakers -- Occupational analysis of nineteenth-century Scottish Quakers -- Changes in individuals' occupations -- The occupations of nineteenth-century Scottish Quakers -- Families and family relationships in Scotland, 1800-2000 -- The Society of Friends in Scotland at the beginning of the twenty-first century -- Survey methodology -- The organisation of the Society of Friends in Scotland -- Gender distribution -- Age distribution -- Religious background -- Involvement in the meeting -- Education and employment of Scottish friends at the beginning of the twenty-first century -- XE "Quakers, Scotland : education" education employment -- XE "Quakers, Scotland : occupations" -- Occupations